PENDIDIKAN SPIRITUAL SEBAGAI BENTENG TERHADAP KENAKALAN REMAJA - Suwaibatul Aslamiah (IAIN Langsa, 2017)
The elements of spiritual education contained in the history of Prophet Yusuf peace be upon him are the value of believing, attitude (manner), persevere and pathnership. And the elements of spiritual education contained in the history of the Prophet Yusuf peace be upon him as a fortress for the juvenile delinquency is character formation that begins with the value of believing so that all deeds done aims of worship. Furthermore, moral values such as patience, humility, courtesy and virtuous, to avoid misconduct that can damage the soul such as brawls, drugs, free sex and porn sites in the world of internetization. Likewise with the value of a persevere to see the difference with the wise, to do not blame each other, and disbelieve another to avoid the enmity of mankind. And lastly pathnership (brothership) values by applying gentle, not arrogant and loving attitude, and also the value of pathnership (brothership) in creating wihdah (unity), quwwah (strength) and mahabbah (love and compassion).